2019
DOI: 10.29312/remexca.v10i8.1548
|View full text |Cite
|
Sign up to set email alerts
|

Biofertilizantes de rizobacterias en el crecimiento de plántulas de chile Poblano

Abstract: El chile Poblano (Capsicum annuum L.) es una variedad muy consumida en nuestro país, pero existen varios problemas que afectan su cultivo y producción. Considerando lo anterior, el objetivo de esta investigación fue elaborar y comparar el efecto de dos biofertilizantes con rizobacterias en el crecimiento de plántulas de chile Poblano. La investigación se realizó en el Colegio de Postgraduados, Campus Montecillo en los años 2015-2016. El trabajo se desarrolló en tres etapas: 1) selección de medios de cultivo y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
2
Order By: Relevance
“…The effect of both types of bioinoculants on poblano chili seedlings (Capsicum annum L.) was also evaluated. In this case, the best results were observed with the encapsulated strains [81]. This suggests that the success in using peat as a support material for solid formulations depends on the conditions in which the bioinoculum will be used and the availability of other strategies.…”
Section: Solid Formulationmentioning
confidence: 83%
See 1 more Smart Citation
“…The effect of both types of bioinoculants on poblano chili seedlings (Capsicum annum L.) was also evaluated. In this case, the best results were observed with the encapsulated strains [81]. This suggests that the success in using peat as a support material for solid formulations depends on the conditions in which the bioinoculum will be used and the availability of other strategies.…”
Section: Solid Formulationmentioning
confidence: 83%
“…In a study by Quiroz Sarmiento et al [81], the effectiveness of peat was evaluated with the following bacteria: Serratia liquefaciens CPAC53, S. plymuthica CPPC55, P. tolaasii P61 and P. yamanorum OLsSf5, in comparison with the encapsulation of the strains using alginate beads. Following a storage period of 150 days, the results showed that the encapsulated strains maintained the highest population.…”
Section: Solid Formulationmentioning
confidence: 99%
“…El ácido indolacético (AIA) producido por la cepa inoculada es la principal fitohormona que induce el crecimiento de las plantas, al aumentar la división celular y la diferenciación de los tejidos (Bhattacharyya y Jha, 2012;Glick, 2012). En el caso de chile poblano el incremento en crecimiento fue de 35% con respecto al testigo por el efecto de la inoculación con bacterias promotoras de crecimiento entre ellas P. tolassi (Quiroz-Sarmiento et al, 2019).…”
Section: Variables Agronómicasunclassified
“…De P. tolaasii se tienen pocos reportes que indiquen su potencia como RPCV en chile, esta cepa aislada y caracterizada por propiedades bioquímicas específicas y promotora de crecimiento (Quiroz-Sarmiento et al, 2019), está siendo evaluada en varios cultivos. La hipótesis que se plantea en el presente estudio es que la inoculación de P. tolaasii combinada con té de vermicompost favorece el desarrollo agronómico y nutritivo de plántulas de chile serrano.…”
Section: Introductionunclassified